Modelling past, present and future Ecosystem Services supply in a protected floodplain under land use and climate changes - Gaglio, M. (2021)
The understanding of protection initiatives’ effects on the delivery of Ecosystem Services (ESs) is of paramount importance to attain sustainable management in Protected Areas (PAs). Protected floodplains provide important ESs to local populations such as water flow regulation and climate regulation through carbon storage. This study investigates the effects of biodiversity protection initiatives (i.e. declaration of Protected Areas – PAs) and the related spatio-temporal land use/land cover (LULC) changes on ecosystem services (ESs) in the Nature Reserve of Paul do Boquilobo – NRPB (Central Portugal). Special focus was made on climate mitigation (i.e. carbon storage and sequestration) and water-related (flood mitigation, water regulation and supply) ESs. The analysis was performed using InVEST model. Three dates of past LULC conditions were considered in the analysis (1967, 1990 and 2015). Moreover, two future alternative LULC scenarios for 2050 were designed (a “Business”- BUS and a “Naturalization”- NAT scenario). The BUS scenario considers a LULC distribution towards high productive agricultural systems, considering only a restricted central core of natural areas, while the NAT scenario considers full coverage of natural areas. The two future extreme LULC scenarios were analyzed considering both no climate change and climate change effects on water-related services based on the pessimistic rcp8.5 climatic scenario. The results showed that PA declaration of NRPB after 1980 increased carbon storage-sequestration and flood mitigation (higher water storage, lower recharge and runoff). The analysis of future LULC scenarios demonstrated that the complete renaturing in combination with climate change (reduction of precipitation, increase of temperature) may lead to severe reduction of recharge and runoff. These results indicate that conflicts may appear between specific water regulation services by the application of PA initiatives in places where groundwater resources are limited or minimum ecological flows in surface waters are difficult to be preserved.